Blueprint Pengembangan Lanjutan Usaha Budidaya Ikan Nila Mashas - MuhammadHasyimN07 NURYADIN (Pasca Sarjana Universitas Satya Negara Indonesia, 2026)
This research addresses the strategic development of MASHAS, a tilapia seed breeding business in Sleman, Yogyakarta. Despite its potential, the business faces challenges in operational standardization and market expansion. This study aims to design a comprehensive business development blueprint to enhance sustainability and competitiveness. The research method employs a qualitative and quantitative approach, utilizing PESTLE and SWOT analysis to evaluate internal and external environments, alongside the Balanced Scorecard and Ansoff Matrix for strategic formulation. The results indicate that MASHAS is economically feasible with an R/C ratio of 1.98 and a survival rate exceeding 80%. However, improvements are needed in human resource management and financial separation. The conclusion suggests that implementing a structured blueprint focusing on SOP standardization and digital market penetration is essential for long-term growth. This study provides a practical framework for small-scale aquaculture businesses to scale their operations effectively.